Impact of sustainability on financial distress: Using profitability as moderator in the banking sector - Kashyap, Samiksha; Rastogi, Shailesh; Nanda, Neena; Parashar, Neha; Dani, Asmita (International Journal of Management and Sustainability, 2025)
Stakeholders in the banking sector are now prioritizing involvement. Nowadays, a solid investment plan considers ESG factors when making investment decisions to reduce risk and produce long-term advantages for investors. The main aim of this study is to appraise the impact of ESG on financial distress by using the net interest margin as a moderator in India’s banking sector. This study uses twelve years (2012–2023) of data with cross-sectional units of twenty-three Indian banks. Quantile panel data regression analysis is used to investigate the results. The findings of this research include the observation that FD is unaffected by ESG and social scores. On the other hand, FD is impacted by environmental and governance scores. NIM affects the relationship between environmental score, social score, and FD. However, it does not affect the relationship between ESG, governance score, and FD. This study provides helpful insights for banks to improve their financial health.